Trade diversion and labor market adjustment: Vietnam and the U.S.-China trade war - Karin Mayr; Gaia Narciso; Dang Duc Anh; Hien Phan (Johannes Kepler University of Linz, Department of Economics, 2023)
This paper investigates the effects of the U.S.-China trade war on trade diversion and the labor market in a third country, Vietnam. We exploit variation in Vietnamese exports to the U.S. across industries and districts based on the extent of the U.S. tariff hikes on Chinese imports and provide evidence of a positive effect on labor market outcomes in Vietnam. Vietnamese workers and districts that are more exposed to the trade war display higher employment, working hours, and wages as a result. Our findings reveal that bilateral trade policy can have substantial offsetting effects on trade flows and labor markets in third countries.
Keywords: F14; F16; R23; 330; trade diversion; trade war